Persamaan Struktur Loyalty Modelling Pengguna Public Transport Railway MRT- SBK Greaters Kuala Lumpur Malaysia - Das, Amsori M (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
In the context of transportation, the passenger loyalty is a measurement of the level of passenger’s willingness to use a similar public transport. The goal of this study is to examines and identifies factors that influencing passenger loyalty. Three factors such as satisfaction, service value, services quality was predicted as an influential factor towards passengers’ loyalty. The Mass Rapid Transit (MRT) for Sungai Buloh to Kajang (SBK) line in Kuala Lumpur conurbation was used as a case study and 555 respondents have contributed to this study. Structural equation modelling (SEM) was used to investigate the relationship between service quality, service value, passenger satisfaction and passenger loyalty. Satisfaction has the most significant influence on passenger loyalty. Service value has direct and positive effects on passenger loyalty. This study also found the service quality has significant indirect effect on the passenger loyalty via service value and passenger satisfaction.The structural model for investigating the loyalty of MRT-SBK users to this service has been analysed and tested using the service quality, satisfaction and quality value showed 75% positive change for all variables. These models recorded average errors and absolute index evaluation in accepted criteria of ≤ 0.09 and ≥ 0.94 respectively. The study reveals that MRT-SBK passengers’ loyalty is significantly influenced by service attributes, such as vehicle safety, convenience, punctuality, comfort, cleanliness of the facility provided. This study helps MRT service provider to optimize resource to enhance user’s satisfaction and therefore, increase the passenger loyalty